A THE FUNCTIONALITY OF THE MIDDLE VALUE OF THE INDONESIAN VERSION OF EMOTIONAL LEARNING INSTRUMENT - Erwin Sulaeman; Wardani Rahayu; Erdawaty Kamaruddin; Winona Amanda Tiara Widodo (LPPM Universitas Negeri Jakarta, 2020)
This article discusses the psychometric validity of the Indonesian version of emotional learning instruments with a scale of five and four response categories. The purpose of this study is to produce an Indonesian version of emotional learning instrument with an effective response category scale used by Indonesians. The instrument is a modification of the scale of the Learning Environment Research Questionnaire on Emotional Climate Classroom. This study is a survey of 1494 responses of 7th and 8th grade junior high school students. Samples were selected by random sampling and based on considerations of schools implementing the 2013 Curriculum. Modification instruments consisting of 43 items were tested in obtaining validity based on item difficulty estimations and psychometric criteria with Rasch modeling. The results of this study indicate that the Andrich threshold validity testing meets the monotonic characteristics and the Standardized Residual Correlation is higher, so the scale of the five response categories is more effective to measure the Indonesian version of emotional learning instruments than the scale of the four response categories. Keywords: Functionality of middle value, ELVI, Rasch Modeling